Risk management towards performance of agropreneur firm: The case of sustainable environmental in Malaysia - Rashid, Intan Maizura Abd; Razak, Noraznira Abd; Shafiai, Syahiru; Zaini, Mohd Rasdi; Esquivias, Miguel Angel (Asian Journal of Agriculture and Rural Development, 2024)
The study examined the correlation between risk management and sustainability of environmental performance. Researchers have determined that risk management has aided firms in enhancing their long-term practices and operations. Sustainability and risk management now align due to their shared overreaching goals. According to the research, green risk management is the most effective method for minimizing risks and improving sustainability. The primary goal of green risk management is to reduce financial risks and increase financial sustainability for the firm performance, especially in the agriculture sector. The finding shows that enterprise risks provide a significant impact on sustainable performance of Agropreneur by t value stands at 3.284. Lastly, the significant indirect effects 95% Boot confidence interval (CI): [Lower Level = 0.090, Upper Level = 0.416] did not straddle a 0 in between, indicating the existence of mediation relationship. Thus, this testing concluded that enterprise risk had a significant mediation effect between intangible resources and Agropreneur sustainable performance relationships.